Growth of ³He crystals at different magnetic fields - Bueno, J.; Blaauwgeers, R.; Parshin, A.Y.; Jochemsen, R. (Физика низких температур, 2008)
The experiments on ³He crystal growth are carried out in magnetic field up 9 T. The data were analyzed
and compared with the results found at zero magnetic field. It was found that the interface and the crystal lattice
couple weakly in the presence of an external magnetic field, and we could set an upper limit of the step
energy of the <110>, <100> and <211> facets at different magnetic fields.